INTRODUKSI TANAMAN SELA BENGKUANG DAN SENTROSEMA PAD A KEBUN LADA PERDU - ANIS TATIK MARYANI (Jurnal Ilmiah Pertanian, 2008)
ABSTRACTIntroduction of yam bean and centrosema as companion crop at bushypepper plantation. Study was conducted from June 2003 to February 2004 at theBogor Agricultural University Experimental Farm, Dramaga – Bogor.The result showed than introduction of companion crops increased the yieldof bushy pepper. Yam bean in the short-term, was better than centrosema ascompanion crop of bushy pepper due to its high content of nitrogen. However, inthe long-term centrosema was better as shown by the higher yield of pepper